Telemedicine in Pakistan – Future of Healthcare Services - Iqbal Hussain Udaipurwala (Journal of Bahria University Medical and Dental College)
“Telemedicine is the practice of medicine over a distance, in which interventions, diagnoses, therapeutic decisions, and subsequent treatment recommendations are based on patient data, documents and other information transmitted through telecommunication systems”